Ecological risk assessment of pesticides on soil biota: An integrated field-modelling approach. (June 2023) - Mu, Hongyu; Yang, Xiaomei; Wang, Kai; Tang, Darrell; Xu, Wen; Liu, Xuejun; Ritsema, Coen J.; Geissen, Violette
Abstract: Pesticide residues in soils can cause negative impacts on soil health as well as soil biota. However, research related to the toxicity and exposure risks of pesticides to soil biota are scarce, especially in the North China Plain (NCP) where pesticides are intensively applied. In this study, the occurrence and distribution of 15 commonly used pesticides in 41 fields in Quzhou county in the NCP were determined during the growing season in 2020. The ecological risks of pesticides to the soil biota, including earthworms, enchytraeids, springtails, mites and nitrogen mineralization microorganisms, were assessed using toxicity exposure ratios (TERs) and risk quotient (RQ) methods. Based on pesticide detection rates and RQs, pesticide hazards were ranked using the Hasse diagram. The results showed that pesticides were concentrated in the 0–2 cm soil depth. Chlorantraniliprole was the most frequently detected pesticide with a detection rate of 37%, while the highest concentration of 1.85 mg kg −1 was found for carbendazim in apple orchards. Chlorpyrifos, carbendazim and imidacloprid posed a chronic exposure risk to E. fetida, F. candida and E. crypticus with the TERs exceeding the trigger value. Pesticide mixtures posed ecological risks to soil biota in 70% of the investigated sites. 47.5% of samples were ranked as high-risk, with the maximum RQ exceeding 490. According to the Hasse diagram, abamectin, tebuconazole, chlorantraniliprole and chlorpyrifos were ranked as the most hazardous pesticides for soil biota in the study region, indicating that alternative methods of pest management need to be considered. Therefore, practical risk mitigation solutions are recommended, in which the use of hazardous pesticides would be replaced with low-risk pesticides with similar functions from the Hasse diagram, or with biopesticides. Graphical abstract: Image 1 Highlights: Nearly half of samples showed high ecological risk to soil biota due to pesticides. Eisenia fetida suffered exposure risk from multiple pesticides. Higher ecological risks were found in apple and wheat-maize rotation fields. A pesticide hazard ranking model was proposed based on the Hasse diagram.